Going to the doctor - Civardi, Anne.; Bates, Michelle; Cartwright, Stephen, 1947- (Tulsa, Okla. : EDC Pub., 2005)
Mrs. Jay takes her children, Joey, Jenny, and Jack, to the doctor. Teaches children about the different reasons they may have to visit a doctor and what to expect during their appointment.
2.3
K-3
Keywords: Medical care -- Fiction; Medical care -- Fiction